Motivasi Kerja Perempuan Di Mini Plants Suppa dalam Meningkatkan Kesejahteraan Keluarga Di Kecamatan Suppa Kabupaten Pinrang - Nurul Fajriani; Wasliha Amir (Institut Agama Islam Negeri Parepare, 2022)
Motivation is an impulse that makes humans capable of acting and doing something. Women who work must have motivation so they are able to do a job. This research aims to determine the work system and factors that influence women's work motivation at Mini Plant Suppa as well as work motivation in improving the family welfare of workers at Mini Plant Suppa. This research uses a descriptive qualitative method by looking at the motivation of workers using Abraham Maslow's 5 Hierarchy of Needs theory and looking at the level of family welfare from the stages and indicators of a prosperous family according to the BKKBN (National Family Planning Coordinating Board). The data collection techniques used were observation, interviews and documentation. Factors that influence women's work motivation at Mini Plant Suppa in improving family welfare are divided into; a) goal factors b) driving and will factors, c) responsibility factors, and d) supporting factors. Women's work motivation at the Suppa Mini Plant in improving family welfare is measured using the stages and indicators of a prosperous family according to the BKKBN, namely 10 workers who reach prosperous family stage I, 9 people in prosperous family stage II, 2 people in prosperous family stage III, and at the prosperous family stage III Plus, it is known that workers have not yet reached that stage.